Antigenic and immunogenic spectrum of foot and mouth disease vaccine strain O1 Campos against representative viruses of topotypes that circulated in Asia over the past decade - Galdo Novo, Sabrina (2017)
Identifying vaccine strains to control outbreaks of foot-and-mouth disease virus that could spread to new regions is essential for contingency plans. This is the first report on the antigenic/immunogenic relationships of the South American O1/Campos vaccine strain with representative isolates of the three currently active Asian type O topotypes. Virus neutralization tests using O1/Campos post-vaccination sera derived from cattle and pigs predicted for both species acceptable cross-protection, even after single vaccination, established by r1 values and by expectancy of protection using monovalent or polyvalent vaccines. The results indicate that effective oil vaccines containing the O1/Campos strain can be used against Asian isolates, expanding the scope of O1/Campos strain included in vaccine banks to control emergencies caused by Asian viruses, even on single-dose vaccination, and to cover the need of effective vaccines in Asia during systematic vaccination.